Frederic Riu and Kant’s Critique: Hegel in the Mirror World. - Pagallo, Giulio F. (Journal of Catalan Intellectual History, 2013)
I will introduce and explain in this article the basic features of the philosophy of my friend and colleague at the School of Philosophy at the Universidad Central de Venezuela Frederic (Federico) Riu i Farré (1925-1985). Riu is a thinker of the difference between real experience and rational system, and conceived of philosophy as a kind of sentry of the “Encyclopedia of Unified Sciences”. Hence the critical attention given to the basic ontological positions held by Husserl, Heidegger, Hartmann and Sartre. And hence his return to the examination of the philosophies of Kant and Hegel, in light of the conditions of twentieth century thought.. key words: Frederic Riu, Catalan philosophy, Venezuelan philosophy, exile, phenomenology.